2002
DOI: 10.1046/j.1523-536x.2002.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Persistence of Health Problems After Childbirth: Associations with Parity and Method of Birth

Abstract: Health problems commonly occurred after childbirth with some resolution over the 6 months postpartum. Some important differences in prevalence of health problems were evident when parity and method of birth were considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
292
10
24

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(366 citation statements)
references
References 77 publications
31
292
10
24
Order By: Relevance
“…Nor did delivery outcomes. This is in contrast to previous studies [6,9]. However, to what extent dyspareunia is related to mode of delivery is not well established [5].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Nor did delivery outcomes. This is in contrast to previous studies [6,9]. However, to what extent dyspareunia is related to mode of delivery is not well established [5].…”
Section: Discussioncontrasting
confidence: 87%
“…Dyspareunia occurring during pregnancy and childbirth may be a result of morphological and hormonal changes of the pelvic floor [8,3,6], and has shown to correlate with delivery mode [6,9]. In women breastfeeding, a reduction in estrogen may lead to reduced vaginal lubrication as a response to sexual stimulation [10].…”
mentioning
confidence: 99%
“…These results are in agreement with a study done in the U.S.A, in which it was found a prevalence of 46% and 43% respectively (18) , however, it contradicts those other studies conducted in Europe and in Brazil which found higher incidence of UI in multiparous than in primiparous (8,12,19,20) . The analysis of presented studies have shown that parturitions is a determinant risk factor to urinary incontinence in the postpartum.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, CD is associated with longer hospital stays for both mother and baby [18,19], increased frequency of serious complications during future pregnancies [18], and higher costs [20]. Despite suggestions that elective CD might improve maternal perineal health [21,22], its long-term benefits are unproven [16,23], and its long-term risks have probably been minimized [24,25].…”
Section: Introductionmentioning
confidence: 99%